APPLICATION OF ARTICULATION LEARNING METHOD IN SCIENCE SUBJECTS - Engkom Komara (Journal Of Resource Management, Economics And Business, 2023)
Purpose: This study aims to analyse the impact of the application of Articulation Learning method to the student’s learning outcomes in Science subject. Research Methodology: This study uses Classroom Action Research and Paired t-test by using the pre-test and post-test score. Results: The application of articulation learning method can increase students’ learning outcomes in Science subject. Limitations: This study analyses the impact of Articulation Learning method in science subject for middle school. Contribution: The results contribute to the education field in terms of effective learning model to increase students’ learning outcomes.